Sleep Quality in Patients with Ankylosing Spondylitis - Ece Çınar; Duygu Kerim; Yeşim Kirazlı (Galenos Yayinevi, 2023)
Chronic pain and inflammation, loss of function, immobility and systemic involvement that are all characteristics of ankylosing spondylitis (AS) have been proposed to cause sleep problems. Almost 70-90% of patients with AS are reported to suffer from disturbed sleep. There are many indices that aim to assess quality and duration of sleep in clinical and academic settings. We have carried out a pilot study and enrolled 70 patients with AS and questioned each subject with a single question that assessed their quality of sleep. This question was taken from the 4th item of the Hamilton Anxiety scale and has been previously used in this population. We have asked patients to assess their sleep quality and score it from 0 to 4, 0 denoting no sleep disturbance and 4 denoting very severe sleep disturbance. The question was well understood and answered fast, causing no delay in routine patient care. Almost 90% of our patients reported some level of sleep disturbance. We have found a significant correlation between disease activity measured by Bath Ankylosing Spondylitis Disease Activity index and severity of sleep disturbance (p<0.05, r=0.34). Assessing quality of sleep in the routine clinical setting does not need to take a very long time and carries valuable information regarding patients' physical and mental wellbeing.